2023
DOI: 10.3389/fvets.2023.1243882
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Surgical treatment and long-term successful outcome of a spinal intramedullary vascular malformation in a dog

Abstract: A 3.5-year-old male intact Staffordshire terrier crossbreed dog was presented with a one-week history of progressive paraparesis with fecal and urinary incontinence. Neurological examination was consistent with a T3-L3 myelopathy. A magnetic resonance imaging study revealed the presence of a well-circumscribed hemorrhagic space-occupying lesion at the level of T12, suspected to be a vascular malformation, such as cavernoma or arteriovenous fistula, primary hematoma or hamartoma; less likely considerations incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The high levels of inbreeding in our dogs have led to disease and suffering for too long. For example, the life expectancy of French bulldogs is now only 4.5 years 2 ; researchers have said that, from a health perspective, the pug can no longer be regarded a typical dog; a recent study revealed that 23.5 per cent of Pomeranians have syringomyelia 3 ; and in Norway 12.6 per cent of Gordon setters lose all their claws 4 . These examples represent unnecessary suffering.…”
mentioning
confidence: 99%
“…The high levels of inbreeding in our dogs have led to disease and suffering for too long. For example, the life expectancy of French bulldogs is now only 4.5 years 2 ; researchers have said that, from a health perspective, the pug can no longer be regarded a typical dog; a recent study revealed that 23.5 per cent of Pomeranians have syringomyelia 3 ; and in Norway 12.6 per cent of Gordon setters lose all their claws 4 . These examples represent unnecessary suffering.…”
mentioning
confidence: 99%